Determinación de los costos de producción para la elaboración de artículos de cuero de la curtiembre creaciones garcés, ubicada en el cantón Ambato, provincia de Tungurahua, período 2017. - Telenchana Tubon, Ana Alexandra (2018)
The research project developed within Creaciones Garcés in the city of Ambato, has as its fundamental objective to respond to the problem detected as the lack of determination of production costs that no longer has a single cost system according to the nature and the requirement for the production of leather goods, this has meant that curtiembre did not determine the costs and content of its total utility, the lack of control over the cost elements in each production process causes the company to face a problem that can stop their activities. This research has a quantitative approach and the descriptive method was used for the direct investigation modality. The population was made up of 3 people from the administrative area. Because of the size of the population, a sample was not obtained. In addition, it was applied as a technic the survey and as a tool the questionnaire. A system of production costs was applied with the raw material, labor and the indirect costs of the manufacture were established, which obtained the real production cost of the leather articles that Creaciones Garcés produces this company accepted a new decision-making for the fulfillment of objectives and goals established by the company. A comparison was made of the costs established in the empirical form by the company against the technical costs incurred to improve quality, which resulted in the current representation of the family in its utility generated by the lack of control in the cost elements.